2020
DOI: 10.3389/fphys.2019.01619
|View full text |Cite
|
Sign up to set email alerts
|

Time Irreversibility of Resting-State Activity in the Healthy Brain and Pathology

Abstract: Characterising brain activity at rest is of paramount importance to our understanding both of general principles of brain functioning and of the way brain dynamics is affected in the presence of neurological or psychiatric pathologies. We measured the time-reversal symmetry of spontaneous electroencephalographic brain activity recorded from three groups of patients and their respective control group under two experimental conditions (eyes open and closed). We evaluated differences in time irreversibility in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 109 publications
0
30
0
Order By: Relevance
“…In the context of neuroscience, the environment is constantly driving the brain out of equilibrium and thus the arrow of time is an excellent tool for characterising the non-equilibrium of brain signals. As a result, there has been considerable interest in using production entropy and related concepts to characterise time reversibility of brain signals (Lynn et al ., 2020; Palus, 1996; Sanz Perl et al ., 2021; Zanin et al ., 2019). In contrast to these methods, here we applied Jarzynski’s idea of using a deep learning paradigm to measure the arrow of time in forward and time-reversed time series, compare the two and thus provide a direct measure of the reversibility of brain signals.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of neuroscience, the environment is constantly driving the brain out of equilibrium and thus the arrow of time is an excellent tool for characterising the non-equilibrium of brain signals. As a result, there has been considerable interest in using production entropy and related concepts to characterise time reversibility of brain signals (Lynn et al ., 2020; Palus, 1996; Sanz Perl et al ., 2021; Zanin et al ., 2019). In contrast to these methods, here we applied Jarzynski’s idea of using a deep learning paradigm to measure the arrow of time in forward and time-reversed time series, compare the two and thus provide a direct measure of the reversibility of brain signals.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, when the cortex becomes isolated from the environment, self-generated activity patterns are regular and appear to be reversible in time, as is the case of the high amplitude slow oscillations that emerge during deep sleep or under the effects of certain anesthetic drugs (Sanchez-Vives and Mattia, 2014;Timofeev et al, 2020). While intuitively appealing, the potential link between temporal asymmetry and conscious awareness has remained largely unexplored: few studies to date addressed the reversibility of brain activity time series (Zanin et al, 2020;Deco et al, 2021), and none attempted to link this reversibility to the global state of consciousness. We adopted a data-driven and model-free approach to assess the breaking of temporal symmetry in ECoG time series obtained from non-human primates undergoing different states of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, emerging evidence supports the view that brain dynamics unfold outside of thermodynamic equilibrium, a scenario where the transition probabilities between states in configuration space are asymmetric, the entropy production rate is strictly positive, and neural activity time series are temporally irreversible (Lynn et al, 2020;Sanz Perl et al, 2021;Deco et al, 2021). Moreover, the degree of proximity to equilibrium dynamics carries functional relevance, since it is related to the level of consciousness (Sanz Perl et al, 2021), has been shown to change during the performance of effortful cognitive tasks (Lynn et al, 2020;Deco et al, 2021), and is altered in neuropsychiatric patients (Zanin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The operations in the HCTSA toolbox are based on the assumption of conservation of entropy, as time irreversibility increases when a time series is more entropic across time [35][36][37]. Time irreversibility has been used to characterize ecological, epidemiological, and engineering time series data [33,38,39], as well as to classify normal and pathologic patterns of neural and cardiac activity and of limb movements [40][41][42][43][44][45]. However, time irreversibility has not been considered as a metric to describe social behavior, including the structure of communication signals.…”
Section: Plos Computational Biologymentioning
confidence: 99%